2020
DOI: 10.3390/polym12091900
|View full text |Cite
|
Sign up to set email alerts
|

Application of Network Analysis to Flow Systems with Alternating Wave Channels: Part B. (Superimposed Drag-Pressure Flows in Extrusion)

Abstract: Due to progress in the development of screw designs over recent decades, numerous high-performance screws have become commercially available in single-screw extrusion. While some of these advanced designs have been studied intensively, others have received comparatively less attention. We developed and validated a semi-numerical network-theory-based modeling approach to predicting flows of shear-thinning polymer melts in wave-dispersion screws. In the first part (Part A), we systematically reduced the complexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…While existing equations were mainly designed to estimate the flow rate and viscous dissipation, further attention must be directed towards parameters such as the power consumption, temperature development, and mixing capability. Recent studies have demonstrated how analytical approximations constructed for screw channels of constant geometry can be implemented into a network-based approach to model the axial pressure and temperature development of both conventional and high-performance screws [ 140 , 142 , 164 ]. The development of new approximation methods will be promoted by the advent of data-based modeling and artificial intelligence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While existing equations were mainly designed to estimate the flow rate and viscous dissipation, further attention must be directed towards parameters such as the power consumption, temperature development, and mixing capability. Recent studies have demonstrated how analytical approximations constructed for screw channels of constant geometry can be implemented into a network-based approach to model the axial pressure and temperature development of both conventional and high-performance screws [ 140 , 142 , 164 ]. The development of new approximation methods will be promoted by the advent of data-based modeling and artificial intelligence.…”
Section: Discussionmentioning
confidence: 99%
“…To provide melt-conveying models that are continuous across their full application range, we have recently proposed a hybrid modeling approach [ 133 ]. The novelty of our method lies in the construction of analytical approximation equations from a large number of numerical solutions to scaled flow equations by using symbolic regression based on genetic programming.…”
Section: Approximate Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gần đây, Christian Marschik và các đồng nghiệp cũng dùng lý thuyết lưu chất Newton để thực hiện nghiên cứu của họ. Công bố của họ được chia làm 2 phần, phần A [8] là những nghiên cứu sâu về lý thuyết dòng chảy để làm giảm độ phúc tạp của mô hình toán, phần B [9] trình bày những phát triển mới về dòng chảy kéo trong máy đùn trục vít đơn. Thông số đầu vào quan trọng của họ là đường kính của trục vít, 35 mm, kết quả đầu ra là các phương trình mô tả dòng chảy lưu chất, khó ứng dụng vào thực tế.…”
Section: Giới Thiệuunclassified
“…In the construction of the leakage-flow models, particular attention was paid to their usability in our screw-simulation routine for predicting the conveying behavior of melt-conveying zones. For detailed information, the reader is referred to the following articles and PhD-theses: Aigner [36], Marschik et al [37][38][39], Roland et al [40], and Luger [41].…”
Section: Research Approachmentioning
confidence: 99%